Penerapan Framework Laravel Untuk Efisiensi Pengelolaan Arsip Surat Berbasis Web di MA Baiturrahman - Devi Istikomah; Faruk Alfiyan (Jurnal Informatika dan Komputer, 2026)
As an active educational institution, MA Baiturrahman faces various challenges in managing correspondence archives. The current manual recording system, which involves writing letter data in a traditional agenda book, presents several obstacles that hinder administrative efficiency. This manual approach often results in document damage, data loss, and poorly organized archive storage. Furthermore, the increasing number of letters each year makes this method less effective and prone to errors in recording and retrieving documents. To address these issues, a web-based document archiving system was developed using the Laravel framework and a system development approach based on the Waterfall model. The aim of this research is to design and build a web-based application system to record and manage incoming and outgoing mail archives. The system is expected to enhance work efficiency, accelerate administrative processes, and ensure the neatness, security, and ease of access to archives. The implementation results of this system indicate a 60% improvement in recording efficiency and a 70% reduction in document retrieval time. In addition, user satisfaction testing showed a satisfaction level of 88%. With the introduction of this system, MA Baiturrahman has achieved a more organized, secure, and efficient archiving solution.